Mature megakaryocytes acquire immune characteristics in a mouse model of aplastic anemia - Ashvind Prabahran; Liangliang Wu; Ash Lee Manley; Zhijie Wu; Shouguo Gao; Hiroki Mizumaki; Valentina Baena; Zulfeqhar Syed; Christian A. Combs; Jichun Chen; Xingmin Feng; Neal S. Young (Blood Advances, 2025)
Abstract: Megakaryocytes (MKs) serve diverse roles beyond platelet production, including hematopoietic stem cell maintenance and immune response modulation. In our mouse model of immune bone marrow failure (BMF), we observed the unexpected persistence of MKs despite thrombocytopenia. These MKs exhibited heightened expression of immune activation markers, such as IA-IE and CD53, compared with MKs from healthy controls. Single-cell RNA sequencing analysis (scRNA-seq) revealed upregulation of immune response pathways and downregulation of pathways related to platelet function and homeostasis in MKs from animals with marrow failure (BMF). Electron microscopy demonstrated that these MKs had fewer cytoplasmic extensions, reduced α-granules, and a less developed demarcation membrane system. MKs from BMF animals had reduced ability to produce platelets compared with normal control MKs. Interestingly, when cocultured with BMF-derived T cells, MKs from healthy mice acquired immune characteristics. Functionally, MKs from BMF mice suppressed hematopoietic stem cell colony formation in coculture experiments. Mechanistically, these MKs appeared to act as antigen-presenting cells, capable of T-cell activation. Notably, similar immune activation of MKs was observed in patients with aplastic anemia through scRNA-seq. These findings highlight the immune functions of mature MKs in an alloimmune model of BMF, with potential implications for human aplastic anemia and related hematologic disorders.